2021
DOI: 10.12973/eu-jer.10.1.353
|View full text |Cite
|
Sign up to set email alerts
|

Extended School Time: Impact on Learning and Teaching

Abstract: <p style="text-align: justify;">This paper presents and assesses the effects of an Extended School Time project (ESTp), with a working day of 8 contact hours, that aimed to develop the students as a whole in its academic, artistic, sport, social and human dimensions. Based in active and integrated pedagogical practices, the project promoted the integration of knowledges, curiosity, sense of criticism, creativity, sharing solidarity and the conviviality of students. This project was applied to a 6th grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The integration of activities based on Nautical Sports (Rowing, Sailing, and Canoeing) in Extended School Time projects for Portuguese children (11.2 years) have a role in improving social activities and academic performance. Progress in respect of rules, level of autonomy, awareness of the environment and mutual help is highlighted for the studied students (Cabral et al, 2021). Our results indicate a high confidence given by teachers to rowing and kayak-canoeing, as activities that facilitate the achievement of general and specific competencies related to school programs in the discipline of physical education.…”
Section: Limits and Discussionmentioning
confidence: 61%
“…The integration of activities based on Nautical Sports (Rowing, Sailing, and Canoeing) in Extended School Time projects for Portuguese children (11.2 years) have a role in improving social activities and academic performance. Progress in respect of rules, level of autonomy, awareness of the environment and mutual help is highlighted for the studied students (Cabral et al, 2021). Our results indicate a high confidence given by teachers to rowing and kayak-canoeing, as activities that facilitate the achievement of general and specific competencies related to school programs in the discipline of physical education.…”
Section: Limits and Discussionmentioning
confidence: 61%
“…It was reported that Asian countries with less time spent in school consistently outperform students in Africa and United States students in subjects like math and science which transcend to grooming innovators and producers. It simply means that the amount of time used in schools does not really bring about concrete learning and building problem solvers (Pedro, Francisco, & Ricardo 2021).…”
Section: Long Hours Of Staying In Schoolmentioning
confidence: 99%